APPLICATION OF EMOTIONAL FREEDOM TECHNIQUE (EFT)-BASED RELAXATION TO REDUCE PUBLIC SPEAKING ANXIETY - Fathonah Salim, Aulia Wasilah; Aryani, Farida; Umar, Nur Fadhilah (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
This study examines the description, implementation, and impact of the Emotional Freedom Technique (EFT)-based relaxation in reducing students’ public speaking anxiety at MAN 1 Makassar City. The study’s population consists of 71 students with high and very high public speaking anxiety. The sample includes 7 students in the control group and 7 students in the experimental groups from class XII IPA 6. This research is a quasi-experiment using a pretest-posttest control group design. The research instruments included a public speaking anxiety questionnaire adapted from the theory by Muslimin & Maswan (2021), the Subjective Units of Distress (SUD) scale, observation, and process and outcome evaluation instruments. The data analysis techniques used were descriptive and inferential statistical analysis. The results showed that public speaking anxiety levels in both the control and experimental groups were categorised as high and very high. The treatment implementation included preparation and problem identification, setup, tuning in, tapping sequence, repetition, and role-playing. The Mann-Whitney U test results showed that EFT-based relaxation has a significant effect in reducing public speaking anxiety, with an Asymp. Sig. value of 0.029 ? 0.05. The decision is that H1 is accepted, and H0 is rejected, meaning that EFT-based relaxation can reduce public speaking anxiety among students at MAN 1 Makassar City